A multiscale simulation study of carbon nanotube interactions with designed amphiphilic peptide helices. - Wallace, E; D'Rozario, R; Sanchez, B; Sansom, M (2010)
The dispersion and manipulation of carbon nanotubes (CNTs) are of great importance if we are to utilise the unique properties of CNTs in a range of biological, electrical and mechanical applications. Recently, a designed amphiphilic peptide helix termed nano-1 has been shown to solubilise CNTs in aqueous solution. Furthermore, the peptide is capable of assembling these coated tubes into fibres. We use a multiscale molecular dynamics approach to study the adsorption profile of nano-1 on a CNT surface. We find that nano-1 interacts with a CNT in a preferred orientation, such that its hydrophobic surface is in contact with the tube. The adsorption profile is unchanged upon increasing the number of peptides on the CNT. Interestingly, when few peptides are adsorbed onto the CNT surface we find that the secondary structure of the peptide is unstable. However, the helical secondary structure is stabilised upon increasing the number of peptides on the CNT surface. This study sheds light on the adsorption of peptides on CNTs, and may be exploitable to enhance the selective solubilisation and manipulation of CNTs.